Dose-dependency of dexamethasone on the analgesic effect of interscalene block for arthroscopic shoulder surgery using ropivacaine 0.5%. Issue 9 (September 2015) - Woo, Jae Hee; Kim, Youn Jin; Kim, Dong Yeon; Cho, Sooyoung
<x xml:space="preserve">Abstract</x> BACKGROUND Dexamethasone prolongs the duration of single-shot interscalene brachial plexus block (SISB). However, dose-dependency of dexamethasone as an adjuvant for SISB remains insufficiently understood. OBJECTIVE The objective of this study is to evaluate the effect of different doses of dexamethasone on the duration of SISB using ropivacaine 0.5%. DESIGN A randomised, double-blind controlled trial. SETTING Single university tertiary care centre. PATIENTS One hundred and forty-four patients scheduled for elective arthroscopic shoulder surgery were allocated randomly to one of four groups. INTERVENTIONS Patients received 12 ml of ropivacaine 0.5% in 0.9% saline (control group), or containing dexamethasone 2.5, 5.0 or 7.5 mg for SISB. MAIN OUTCOME MEASURES The primary endpoint was the time to the first analgesic request. Pain scores and adverse effects were also assessed up to 48 h postoperatively. RESULTS Inclusion of dexamethasone 2.5, 5.0 and 7.5 mg resulted in significant (P < 0.001) increases in time to the first analgesic request by factors of 1.6, 2.2 and 1.8, respectively. The percentages of patients not requiring analgesics in the first 48 h postoperatively with dexamethasone 0.0, 2.5, 5.0 and 7.5 mg were 3, 22, 39 and 33%, respectively (P < 0.001). There were no significant effects on pain scores or incidences of adverse effects. CONCLUSION Dexamethasone demonstrated significant beneficial dose-dependent effects on duration to the first analgesic request, the number of patients not requiring analgesics and analgesic use in the first 48 h after SISB for arthroscopic shoulder surgery. There were no significant effects on pain scores or incidences of adverse effects. TRIAL REGISTRATION the trial was registered with the Clinical Trial Registry of Korea: https://cris.nih.go.kr/cris/index.jsp. Identifier: KCT0001078